Characterization and Evaluation of a Commercial WLAN System for Human Provocation Studies. (9th June 2015) - Zentai, Norbert; Fiocchi, Serena; Parazzini, Marta; Trunk, Attila; Juhász, Péter; Ravazzani, Paolo; Hernádi, István; Thuróczy, György
Abstract : This work evaluates the complex exposure characteristics of Wireless Local Area Network (WLAN) technology and describes the design of a WLAN exposure system built using commercially available modular parts for the study of possible biological health effects due to WLAN exposure in a controlled environment. The system consisted of an access point and a client unit (CU) with router board cards types R52 and R52n with 18 dBm and 25 dBm peak power, respectively. Free space radiofrequency field (RF) measurements were performed with a field meter at a distance of 40 cm from the CU in order to evaluate the RF exposure at several signal configurations of the exposure system. Finally, the specific absorption rate (SAR) generated by the CU was estimated computationally in the head of two human models. Results suggest that exposure to RF fields of WLAN systems strongly depends on the sets of the router configuration: the stability of the exposure was more constant and reliable when both antennas were active and vertically positioned, with best signal quality obtained with the R52n router board at channel 9, in UDP mode. The maximum levels of peak SAR were far away from the limits of international guidelines with peak levels found over the skin.